COMPACT GENETIC ALGORITHM FOR CRYPTANALYSISTRAPDOOR 0-1 KNAPSACK CIPHER - Al-Dabbagh, Rawa'a Dawoud Hassan (Al-Nahrain Journal of Science, 2018)
Security is a broad topic and covers a multitude of sins. In its simplest form, it is concerned with people trying to access remote services that they are not authorized to use. Cryptology is the science and studies of systems for secrete communication. It consists of two complementary fields of study: Cryptography and Cryptanalysis. The application of genetic algorithm in cryptanalysis of knapsack cipher is suggested by Spillman. This paper considers a new approach to cryptanalysis knapsack cipher based on the representation of the population as a probability distribution over the set ofsolutions; this is called compact Genetic Algorithm (cGA). Tests have been presented to clarify the results obtained. The results show that cGA achieve the breaking of the ciphertext. Moreover, the comparison among Spillman results, simple GA (sGA) and our results are also provided. The results show that cGA is worth to be considered for the attack of trapdoor 0-1 knapsack cipher.